Pengaruh Likuiditas, Solvabilitas, dan Aktivitas terhadap Kinerja Keuangan PT Unilever Indonesia Tbk yang Terdaftar di Bei Periode 2020–2024 - Diva, Zaira Hanla; Puji Isyanto (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the effect of liquidity ratio (Current Ratio), solvency (Debt to Equity Ratio), and activity (Total Assets Turnover) on financial performance measured by Return on Assets (ROA) at PT Unilever Indonesia Tbk during the period 2020–2024. The company was selected as the subject of this study because it is one of the major players in the Fast Moving Consumer Goods (FMCG) industry, which faces market dynamics and global economic challenges. The method used is a descriptive quantitative approach with multiple linear regression analysis techniques. The data analyzed were obtained from the company's annual financial reports and processed using SPSS version 29. The research results indicate that the Current Ratio (CR) variable does not have a significant effect on ROA, suggesting that high liquidity does not necessarily directly enhance profitability. Conversely, the Debt to Equity Ratio (DER) and Total Assets Turnover (TATO) have a positive and significant effect on ROA. This indicates that an efficient capital structure and productive asset management contribute significantly to improving the company's financial performance. Simultaneously, all three variables were found to have a significant effect on ROA. This study has important implications for company management in making strategic financial decisions focused on strengthening operational efficiency and optimizing capital structure management.